Silencing a phloretin‐specific glycosyltransferase perturbs both general phenylpropanoid biosynthesis and plant development. (8th May 2017) - Dare, Andrew P.; Yauk, Yar‐Khing; Tomes, Sumathi; McGhie, Tony K.; Rebstock, Ria S.; Cooney, Janine M.; Atkinson, Ross G.
Summary: The polyphenol profile of apple ( Malus  ×  domestica ) is dominated by the dihydrochalcone glycoside phloridzin, but its physiological role is yet to be elucidated. Biosynthesis of phloridzin occurs as a side branch of the main phenylpropanoid pathway, with the final step mediated by the phloretin‐specific glycosyltransferase UGT88F1. Unexpectedly, given that UGTs are sometimes viewed as 'decorating enzymes', UGT88F1 knockdown lines were severely dwarfed, with greatly reduced internode lengths, narrow lanceolate leaves, and changes in leaf and fruit cellular morphology. These changes suggested that auxin transport had been altered in the knockdown lines, which was confirmed in assays showing that auxin flux from the shoot apex was increased in the transgenic lines. Metabolite analysis revealed no accumulation of the phloretin aglycone, as well as decreases in many non‐target phenylpropanoid compounds. This decreased accumulation of metabolites appeared to be mediated by the repression of the phenylpropanoid pathway via a reduction in key transcript levels (e.g. phenylalanine ammonia lyase, PAL) and enzyme activities (PAL and chalcone synthase). Application of exogenous phloridzin to the UGT88F1 knockdown lines in tissue culture enhanced axial leaf growth and partially restored some aspects of 'normal' apple leaf growth. Together, our results strongly implicate dihydrochalcones as critical compounds in modulating phenylpropanoid pathway flux and establishing auxin patterning early in apple development. Significance Statement: The polyphenol profile of apple ( Malus  ×  domestica ) is dominated by the dihydrochalcone glycoside phloridzin, however, its physiological role is yet to be elucidated. Our results indicate that perturbing phloridzin accumulation affects normal growth and development in apple via repression of the phenylpropanoid pathway and modulation of auxin transport.